Synthesis and characterization of Zn3Nb2O8nanopowders via a rapid vibro-milling technique - P. Pakawanit (2018)
The simple mixed-oxide method via a rapid vibro-milling technique is explored in the preparation of pure zinc niobate (Zn3Nb2O8) nanopowders. The formation of the phase in the calcined powders has been investigated as a function of calcination conditions by TG-DTA and XRD techniques. Morphology, particle size and chemical composition have been determined via a combination of SEM/TEM and EDX techniques. It has been found that the minor phase of ZnNb2O6tends to form together with the Zn3Nb2O8phase, depending on calcination conditions. More importantly, it is seen that optimization of calcination conditions can lead to a single-phase Zn3Nb2O8in a monoclinic phase. © 2013 Copyright Taylor and Francis Group, LLC.